Efektifitas penerapan pemungutan pajak hotel atas rumah kos dengan jumlah kamar kos lebih dari 10 di Bappenda Sumedang - Istiono, Deni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In Article 1 of Law Number 28 Year 2009 concerning Regional Taxes and Regional Levies, boarding house tax is included in the hotel tax category. Boarding house businesses that have more than 10 rooms are subject to tax of 10%. Boarding house tax in Sumedang Regency has great potential in tax collection, especially local taxes. The purpose of this study is to find out how effective the implementation of hotel tax collection on boarding houses with more than 10 boarding rooms and to find out how the obstacles or constraints experienced by the Sumedang Regency Revenue Management Agency in hotel tax collection for boarding houses. The analytical method used is a quantitative method that is the data on the realization of the boarding house tax with the number of boarding house tax payers in Sumedang Regency from 2015-2019, amounting to 1,288. The results showed that the implementation of boarding house tax collection in Sumedang District had been going well. The level of effectiveness and receipt of boarding house tax has been reached and is classified as effective. From the calculation of the effectiveness of boarding house tax collection in Sumedang Regency in 2015 amounted to 122.63%, in 2016 amounted to 116.01%, in 2017 amounted to 120.95%, in 2018 amounted to 81.56%, and in 2019 amounted to 186 , 76%. And it can be seen that the effectiveness of boarding house tax collection for 2015 is very effective, 2016 is very effective, 2017 is very effective, 2018 is quite effective, and 2019 is very effective. However, the absorption of local taxes from the boarding-lodging sector in Sumedang Regency is still not maximal, even though the boarding house rental business can be called a promising business and also has great potential for increasing Local Revenue.